2018
DOI: 10.2478/acve-2018-0036
|View full text |Cite
|
Sign up to set email alerts
|

Antihelminic Activity of Carvacrol, Thymol, Cinnamaldehyde and P-Cymen Against the Free-Living Nematode Caenorhabditis elegans and Rat Pinworm Syphacia muris

Abstract: In the present study we tested the dose andh time dependence of the antinematodal effects of carvacrol and tyhmol on Caenorabditis elegans, and the efficacy of carvacrol, thymol, p-cymene and cinnamaldehyde,which were administrated in the drinking water of rats naturally infected with the pinworm Syphacia muris. The control treatment of the infected rats was carried out with piperazine. Thymol caused a dose and time-dependent mortality in adult C. elegans. The value of the Median Lethal Concentration (LC50) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…The WVP of the SC film obtained in this study (1.78 × 10 −11 gm −1 s −1 Pa −1 ) was in the range of the published result by Acter et al (2.84 × 10 −11 gm −1 s −1 Pa −1 ) [ 58 ]. It was previously reported that the inclusion of hydrophobic components to biopolymer films resulted in a decreased WVP due to the increased hydrophobicity of the composites [ 6 ]. This was in agreement with the results obtained in this study since the addition of thymol slightly decreased the permeability of impregnated films compared to the controls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The WVP of the SC film obtained in this study (1.78 × 10 −11 gm −1 s −1 Pa −1 ) was in the range of the published result by Acter et al (2.84 × 10 −11 gm −1 s −1 Pa −1 ) [ 58 ]. It was previously reported that the inclusion of hydrophobic components to biopolymer films resulted in a decreased WVP due to the increased hydrophobicity of the composites [ 6 ]. This was in agreement with the results obtained in this study since the addition of thymol slightly decreased the permeability of impregnated films compared to the controls.…”
Section: Resultsmentioning
confidence: 99%
“…For the same reasons, instead of synthetic chemicals, mostly molecules of natural origin are preferred to deliver the activity to the food packaging material. Thymol is a colorless, crystalline substance, found in essential oils of thyme, oregano and winter savory with proven antimicrobial effects against Gram-positive and Gram-negative bacteria, and also against some parasites [ 5 , 6 ]. Since it has been “generally recognized as safe” (GRAS) by the Food and Drug Administration (FDA), thymol was found to be a promising bioactive agent for active packaging purposes [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of course, many other botanicals have been studied for the nematicidal properties of their yielding EOs [17][18][19], while nanotechnology has made progress in the introduction of EOs into open field conditions [20][21][22]. However, there are few studies on the ecotoxicological effects of biopesticides accompanying biological activity, and so, notwithstanding their natural origin, they may as well have unknown effects on the environment and non-target organisms [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Carvacrol is known for its wide use in traditional pharmacopeia due to antimicrobial and disinfectant properties [15][16][17]. In addition, some studies previously indicated that carvacrol has antinematodal properties against pathogenic helminths such as the pig roundworm Ascaris suum [18], the sheep parasite Haemonchus contortus [19,20], the fish parasite Anisakis simplex [14,21] and plant parasitic nematodes [22], and it can also kill the free-living model nematode Caenorhabditis elegans [23][24][25]. However, the antiparasitic mode of action of monoterpenoid compounds is poorly understood, and their potential use against horse parasites has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%